Building the future One Health workforce in Eastern and Southern Africa: Gaps and opportunities - Yussuf, Buke; Richards, Shauna; Grace, Delia; Mutie, Ianetta; Caron, A.; De Nys, H.; Goregena, B.; Kgosimore, M.; Kimaro, E.; Qekwana, N.; Tadesse, Y.; Knight-Jones, Theodore J.D.; et al. (CAB International, 2025)
The Quadripartite comprised of the Food and Agriculture Organization (FAO), World Health Organization (WHO), World Organisation for Animal Health (WOAH), the United Nations Environment Program (UNEP), and the One Health High Level Expert Panel collectively support enhancing the One Health (OH) capacities of the workforce addressing OH issues; however, competencies for this workforce are not generally agreed upon, applied uniformly, or always relevant in the global South. The objectives of this study were to (1) develop an inventory of OH education offered by higher education institutes in Eastern and Southern Africa, and (2) define OH competencies relevant for OH training in Eastern and Southern Africa. A survey in 11 Eastern and Southern African countries was conducted with OH key informants purposively selected from higher education institutes offering OH education (n = 1–3/higher education institutes). Snowball sampling was used to identify additional higher education institutes/individuals. Results were validated by OH country representatives. Data were collected using questionnaires, and descriptive statistics were used to present the results. Forty-two questionnaires were completed from 29 higher education institutes, and 166 OH education interventions were reported with 69% being courses contributing to a degree, 21% as degree/diploma awarding, and the remainder were missing data (n = 16). Masters were the most common OH degree program of which the highest number of students taught were from public health/OH, food safety, and applied epidemiology. There are many OH educational courses and activities on offer in Eastern and Southern Africa; however, their total breadth is difficult to assess due to limited awareness of the availability of OH education not only between higher education institutes in a country but also even within a higher education institute between faculties. Numerous cross-cutting and technical competencies were considered essential to work in OH; however, this level of expertise is rarely logistically possible to provide in any single degree program. For OH education to be consistently applied, competency frameworks that are relevant to a region are necessary. Technical competencies are important from a disciplinary context; however, necessary cross-cutting competencies should be a focus in developing the future OH workforce.